2014
DOI: 10.1002/jmr.2357
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the MDP binding and CARD-CARD interaction in zebrafish (Danio rerio) NOD2: a molecular dynamics approach

Abstract: Nucleotide binding and oligomerization domain (NOD2) is a key component of innate immunity that is highly specific for muramyl dipeptide (MDP)-a peptidoglycan component of bacterial cell wall. MDP recognition by NOD2-leucine rich repeat (LRR) domain activates NF-κB signaling through a protein-protein interaction between caspase activating and recruitment domains (CARDs) of NOD2 and downstream receptor interacting and activating protein kinase 2 (RIP2). Due to the lack of crystal/NMR structures, MDP recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 97 publications
(168 reference statements)
1
41
0
Order By: Relevance
“…NOD1 CARD showed an extensive negative surface and a small positively charged patch; however, RIP2 CARD portrayed several positive and negative patches over the surface (Fig 1B and 1C). Owing to the interest of this study, two potential type-I surface patches (both positive (α1 and α4; type-Ia) and negative (α2 and α3; type-Ib)) were identified on the basis of earlier reports on NOD1/NOD2-RIP2 and Ap1-C9 CARD-CARD interaction [1520,23,24,33,34]. The binding patches including the critical/surface exposed residues (experimentally proved/predicted) were illustrated in Fig 1C–1E.…”
Section: Resultsmentioning
confidence: 99%
“…NOD1 CARD showed an extensive negative surface and a small positively charged patch; however, RIP2 CARD portrayed several positive and negative patches over the surface (Fig 1B and 1C). Owing to the interest of this study, two potential type-I surface patches (both positive (α1 and α4; type-Ia) and negative (α2 and α3; type-Ib)) were identified on the basis of earlier reports on NOD1/NOD2-RIP2 and Ap1-C9 CARD-CARD interaction [1520,23,24,33,34]. The binding patches including the critical/surface exposed residues (experimentally proved/predicted) were illustrated in Fig 1C–1E.…”
Section: Resultsmentioning
confidence: 99%
“…The putative binding residues for the Nod2:MDP interaction were described in the Nod2 crystal structure 23 and Nod2 models 33 . From these models, three residues were selected as critical binding residues of interest, R877, W931 and S933 (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…It has a C-terminal leucine-rich repeat region for sensing microbial products, a central nucleotide-binding domain (NACHT), and an N-terminal CARD (caspase activation and recruitment domain) [3] . In antigen-presenting cells, NOD2 expression leads to downstream activation of innate pathways of host defense [4] when triggered by its interaction with Muramyl Dipeptide (MDP), a component of gram-positive and -negative bacterial cell walls, subsequently leading to the activation of the pro-inflammatory NF-κB pathway. Several studies have identified three NOD2 SNPs (Arg702Trp, SNP8; Gly908Arg, SNP12; Leu1007fsinsC, SNP13) [5] as being associated with increased incidence and severity of aGvHD, increased TRM, and reduced Overall Survival (OS) [6,7] .…”
Section: Introductionmentioning
confidence: 99%